PENGARUH METODE PEMBELAJARAN PENEMUAN TERBIMBING DAN KREATIVITAS TERHADAP HASIL BELAJAR IPA SISWA SDN NO. 105292 BANDAR KLIPPA KABUPATEN DELI SERDANG - Rinci Simbolon (JURNAL TEMATIK, 2015)
Influence of Guided inquiry Learning Method and Creativity for Science Learning outcomes of Students  Elementary School No. 105292 Bandar Klippa regency Deliserdang. This research aims to determine: (1) the influence of the guided inquiry learning  and expository method for science learning outcomes of students; (2) the influence of creativity for science learning outcomes of students; and (3) the interaction between  the learning method and creativity for science learning outcomes of students. This research was conducted for students Elementary School No 105292 in 2014/2015 academic year. The sampling technique used by  random sampling, so that this study sample in each study group consist of 27 people for the experimental and 26 control group. The research method which is used  a quasi experiment with 2 x 2 factorial. Analysis technique which is used is the variance analysis of two lanes with a significant level α = 0.05 by F test, Barlett test, Future test use Scheffe test. The findings show: (1) there is a significant of the learning method  for science learning outcomes of students in SDN No 105292 of Bandar Klippa ( F count> F table = 4.39> 4.04); (2) there are significant of creativity for science learning outcomes of students in SDN No 105292 of Bandar Klippa (Fcount> F table = 32.93> 4.04); (3) there is a significant  interaction between teaching method and creativity for science learning outcomes of students in SDN No 105292 Bandar Klippa, A1B1 = 91.43 and A1B2 = 78.54 while A2B1 = 84.07 and A2B2 = 79.75. 2x2 factorial ANAVA calculation results obtained on calculations Fh = 8.60 and  Ft = 4.04 confidence level α = 0.05 so it can be expressed Fh (8.60)> Ft (4.04), the hypothesis has been verified by this research.